Collector and philatelic press in the RSFSR/USSR during the first half of the 1920s: From pluralism to monopolism - A.V. Yakub; N.V. Yakub (Ученые записки Казанского университета: Серия Гуманитарные науки)
Periodicals is a “mirror” of society. On the one hand, they reflect the social and cultural climate of a particular historical epoch. On the other one, retain the memory of the past times. Magazines and newspapers can influence the public opinion and provide feedback in the management of society through the prism of ideology and propaganda, thereby serving the interests of the state. This paper considers collector periodicals of the Soviet Russia in the first half of the 1920s. During this period, all printed materials were either private or state-owned. The publishing development and the editorial attitudes in the collector periodicals of that time were determined by the Soviet reality and reflected it. For this reason, the Soviet collector periodicals, including philatelic magazines, serve as an invaluable source of evidence of the growing pressure produced by the party policies in propaganda, agitation, and publishing industry. A number of periodicals that received little support from the state were unable to engage in any pro-active resistance. In the early 1920s, the number of collector periodicals rocketed. By the end of 1922–first half of 1923, the dialog between them finally turned into a monologue of one edition promoting the positions of the state. As a result, the privately owned collector magazines disappeared. The remaining magazine turned out to perform mostly ideological and educational functions. Therefore, the general tasks and problems of collecting, in particular the philatelic ones, were replaced by the vital economic problems making the collector periodicals a tool used for bringing up an ideal Soviet person.